2021
DOI: 10.21203/rs.3.rs-518655/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Learning Loss During COVID-19: An Early Systematic Review

Abstract: With COVID-19 having caused significant disruption to the global education system, researchers are beginning to become concerned with the impact that this has had on student learning progress and, in particular, if learning loss has been experienced. To evaluate this, we conduct a thorough analysis of recorded learning loss evidence documented between March 2020 and March 2021. This systematic review aims to consolidate available data and document what has currently been reported in the literature. Given the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(8 citation statements)
references
References 9 publications
2
4
0
1
Order By: Relevance
“…Taking into account our previous theoretical considerations (see Section 1), two explanations for these results suggest themselves: on the one hand, the lower ratings could reflect an actual deficit in knowledge acquisition during distance learning. This explanation would be in line with those empirical findings that have now clearly shown that the unprepared switch to distance learning has been problematic for the learning success of school and university students due to limited opportunities of communication, technical difficulties and/or a lack of abilities regarding self-regulated learning [15,57,58,82,100,101]. On the other hand, the lower scores of the group surveyed after switching to distance learning could also be attributed to difficulties in validly rating their own abilities, caused by diminishment of the social dimension of comparison that is decisive for the development of a stable and realistic academic self-concept [23,24].…”
Section: Studysupporting
confidence: 83%
“…Taking into account our previous theoretical considerations (see Section 1), two explanations for these results suggest themselves: on the one hand, the lower ratings could reflect an actual deficit in knowledge acquisition during distance learning. This explanation would be in line with those empirical findings that have now clearly shown that the unprepared switch to distance learning has been problematic for the learning success of school and university students due to limited opportunities of communication, technical difficulties and/or a lack of abilities regarding self-regulated learning [15,57,58,82,100,101]. On the other hand, the lower scores of the group surveyed after switching to distance learning could also be attributed to difficulties in validly rating their own abilities, caused by diminishment of the social dimension of comparison that is decisive for the development of a stable and realistic academic self-concept [23,24].…”
Section: Studysupporting
confidence: 83%
“…Capturing actual impacts on learning may take years, but there are ongoing efforts to capture emergent learning losses using both objective and proxy measures (Ofsted 2020a, b, c;Sharp et al, 2020;UNESCO et al, 2020). Early findings from Australia, Europe, the UK and the US show that although not all children have experienced learning losses, many children have lost between one and five months of learning (Education Endowment Foundation (EEF), 2020; Patrinos & Donnelly, 2021), while simulations project up to one year or more of learning loss in some LICs (Angrist et al, 2021). Differences have emerged across subject areas and age groups, while socioeconomically disadvantaged and racially marginalised learners have often experienced greater losses (EEF, 2020;Patrinos & Donnelly, 2021).…”
Section: Theoretical and Methodological Framingmentioning
confidence: 99%
“…Early findings from Australia, Europe, the UK and the US show that although not all children have experienced learning losses, many children have lost between one and five months of learning (Education Endowment Foundation (EEF), 2020; Patrinos & Donnelly, 2021), while simulations project up to one year or more of learning loss in some LICs (Angrist et al, 2021). Differences have emerged across subject areas and age groups, while socioeconomically disadvantaged and racially marginalised learners have often experienced greater losses (EEF, 2020;Patrinos & Donnelly, 2021). Measuring actual learning losses systematically is proving challenging due to a lack of assessment standardisation (Middleton, 2020), a lack of system-wide approaches (UNESCO et al, 2020) and inaccurate/incomplete results due to missing assessment data, low response rates and sampling biases (Crenna-Jennings et al, 2021;Wyse et al, 2020).…”
Section: Theoretical and Methodological Framingmentioning
confidence: 99%
See 1 more Smart Citation
“…( 2022 ), Hammerstein et al. ( 2021 ), König und Frey ( 2022 ), Patrinos und Donnelly ( 2021 ) und Zierer ( 2021 ) geben einen Überblick über Leistungsstudien, die die Frage nach Lerneinbußen und neuer Bildungsungleichheit aufgrund der pandemiebedingten Schulschließungen im Frühjahr 2020 zu beantworten versuchen. 1 Nimmt man die Befunde der in den Überblicksarbeiten enthaltenen Studien (z.…”
Section: Auswirkungen Von Schulschließungenunclassified